Predicting the pain continuum after adolescent idiopathic scoliosis surgery: A prospective cohort study. (27th March 2017) - Chidambaran, V.; Ding, L.; Moore, D.L.; Spruance, K.; Cudilo, E.M.; Pilipenko, V.; Hossain, M.; Sturm, P.; Kashikar‐Zuck, S.; Martin, L.J.; Sadhasivam, S.
Abstract: Background: Chronic postsurgical pain (CPSP) affects half a million children annually in the United States, with dire socioeconomic consequences, including long‐term disability into adulthood. The few studies of CPSP in children are limited by sample size, follow‐up duration, non‐homogeneity of surgical procedure and factors evaluated. Methods: In a prospective study of 144 adolescents undergoing a single major surgery (spine fusion), we evaluated demographic, perioperative, surgical and psychosocial factors as predictors of a continuum of postsurgical pain: immediate, pain maintenance at 2–3 months (chronic pain/CP) and persistence of pain a year (persistent pain/PP) after surgery. Results: We found an incidence of 37.8% and 41.8% for CP and PP. CP and acute pain were both significant predictors for developing PP ( p ‐value <0.001 and 0.003). Preoperative pain and higher postoperative opioid requirement was significantly associated with CP ( p  = 0.015, p  = 0.002), while Childhood Anxiety Sensitivity Index ( p  = 0.002) and surgical duration ( p  = 0.014) predicted PP. The final regression models had reasonable predictive accuracy (c‐statistic of 0.73 and 0.83 for CP and PP, respectively). Anxiety scores and catastrophizing for child and parent were found to be significantly correlated ( p  = 0.005, p  = 0.013 respectively). Pain trajectories revealed that 65% of patients who developed PP reported CP and high pain trends; however, 33% of those who developed PP could not be identified using solely pain criteria. Conclusion: Persistent postsurgical pain in children is a significant problem. It can be predicted in part by combinations of psychological and clinical variables, which may provide evidence‐based measures to prevent development of CPSP in the future. Significance: In a homogeneous cohort of adolescents undergoing spine fusion, we report a high incidence of persistent postsurgical pain (41.8%) predicted by child anxiety, perioperative pain, and surgical duration. Our results stress timely preventive and therapeutic strategies.